The Pass-Through of Temporary VAT Rate Cuts: Evidence from German Supermarket Retail - Clemens Fuest; Florian Neumeier; Daniel Stöhlker (Center for Economic Studies and Ifo Institute (CESifo), 2021)
On 3 June 2020, the German government announced a temporary value added tax (VAT) rate reduction. VAT rates were reduced on 1 July 2020 and went back to their previous level on 1 January 2021. We study the price effects of the temporary VAT rate reduction using a web-scraped data set covering the daily prices of roughly 130,000 supermarket products. To identify the causal price effects, we compare the development of prices in Germany to those in Austria. Our findings indicate an asymmetric price response to the VAT rate cut and subsequent increase. The reduction of VAT rates led to a price decrease of roughly 1.3%, implying that about 70% of the tax cut were passed on to consumers. In contrast, the price effect of the VAT increase was only about half that size. We also study the link between tax incidence and the intensity of competition. Pass-through of the VAT reduction was higher in product groups with a large number of competing products. We rationalize this finding by analyzing consumption tax incidence in the `love of variety' model of consumption.
Keywords: E31; H22; H25; 330; value added tax; tax incidence; fiscal policy; price effects; competition